Laboratory characterization of soil internal erosion - Deng, Hao (Nanyang Technological University, 2023)
The performance of subsequent structures which are intended to limit seepage, can be impacted by internal erosion of sensitive granular materials under fluid flow. Present days, suffusion research is the main area of study. Suffusion is the process by which coarser soil particles constructions allow finer soil particles to be designated by seepage flow, often occurring in tandem with seepage flow over time. Through the application of suitable techniques for the preparation and placing of soil specimens together with proper saturation procedures, the feature of the internal erosion test would be examined and evaluated. After conducting a series of laboratory tests, we discovered that the internal clogging would happen in dense instances, that breaking the clogging would be more difficult in cases with a smaller void ratio, and that the permeability of the pre-clogging is larger than that of post-clogging. In contrast, suffusion will happen in loose instances, and permeability will not change in either the pre-suffusion or within suffusion stage. In conditions with higher void ratios, soil specimens have better permeability and are more internally stable. In general, the critical value of hydraulic gradient and pressure which is equivalent to 2 and 3kPa respectively that don’t change when internal clogging of suffusion occurs whether is in dense or loose cases.